2020
DOI: 10.1186/s40792-020-01060-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel Killian–Jamieson diverticulectomy using a thyroid gland flap: a case report

Abstract: Background A Killian–Jamieson diverticulum is a rare pharyngoesophageal diverticulum that is radically treated by diverticulectomy. However, there is no consensus on whether cricopharyngeal myotomy is necessary, and the optimal surgical methods that prevent postoperative complications such as leakage are undetermined. Case presentation A 49-year-old man was referred to our hospital with oropharyngeal dysphagia while eating. The patient was preoperatively diagnosed with a Killian–Jamieson diverticulum based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In contrast, Inoguchi et al and Ebisumoto et al reported that CPM increases the risk of gastroesophageal reflux among patients with swallowing difficulties [12,13]. A previous report suggested that the cricopharyngeal muscle should be preserved in patients with KJD because of the risk of postoperative dysfunction of the muscle, which has the potential to cause issues such as gastroesophageal reflux [14]. CPM also has the potential to cause unnecessary esophageal injury.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Inoguchi et al and Ebisumoto et al reported that CPM increases the risk of gastroesophageal reflux among patients with swallowing difficulties [12,13]. A previous report suggested that the cricopharyngeal muscle should be preserved in patients with KJD because of the risk of postoperative dysfunction of the muscle, which has the potential to cause issues such as gastroesophageal reflux [14]. CPM also has the potential to cause unnecessary esophageal injury.…”
Section: Discussionmentioning
confidence: 99%